Leukocyte Interferon for Treating First Episodes of Genital Herpes in Women - Pazin, George J. (J Infect Dis, 1987)
Women experiencing their first episodes of genital herpes were treated, beginning within three days of the onset of lesions, with 5 × 10(4) units of human leukocyte interferon/kg of body weight for 12 doses over 14 days (total, ∼3.6 × 10(7) units) or with placebo in equivalent volumes. Life-table analysis revealed quicker healing and significant reductions in the duration of shedding of virus in interferon-treated patients. Maximum daily geometric mean titers of virus and total area of unhealed lesions also decreased more quickly. No statistically significant difference in resolution of pain was seen between the two groups. Interferon had no effect on onset or frequency of subsequent recurrences recorded over one year of follow-up. Moderate, transient neutropenia occurred in 13 of 34 interferon-treated patients. A therapeutic effect of human leukocyte interferon on initial genital herpes was documented, but the clinical usefulness of interferon treatment of genital herpes is limited at this time.